1988
DOI: 10.1172/jci113330
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of cell pH by ambient bicarbonate, carbon dioxide tension, and pH in the rabbit proximal convoluted tubule.

Abstract: To study the regulation of cell pH by ambient pH, carbon dioxide tension (Pco2), and bicarbonate (HCO3), cell pH was measured in the isolated, in vitro microperfused rabbit proximal convoluted tubule using the fluorescent dye (2',7')-bis-(carboxyethyl)- (5,6)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0

Year Published

1989
1989
1999
1999

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 40 publications
2
32
0
Order By: Relevance
“…For the analysis of the luminal Na/H antiporter by luminal sodium removal, the solutions were HCO3-free, containing Hepes and 0. i mM acetazolamide in luminal and bath perfusates (solutions 3 and 4, Table I). Previous studies have shown that analysis of luminal transporters is facilitated by effectively blocking the rate of the basolateral transporters, because these latter transporters are more important determinants of cell pH (8,15). We have also demonstrated that the Na/(HCO3)3 cotransporter is fully inhibited in the absence of exogenous C02/HCO3 and 0.1 mM acetazolamide and that acetazolamide does not affect the rate of the Na/H antiporter in this setting (12).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the analysis of the luminal Na/H antiporter by luminal sodium removal, the solutions were HCO3-free, containing Hepes and 0. i mM acetazolamide in luminal and bath perfusates (solutions 3 and 4, Table I). Previous studies have shown that analysis of luminal transporters is facilitated by effectively blocking the rate of the basolateral transporters, because these latter transporters are more important determinants of cell pH (8,15). We have also demonstrated that the Na/(HCO3)3 cotransporter is fully inhibited in the absence of exogenous C02/HCO3 and 0.1 mM acetazolamide and that acetazolamide does not affect the rate of the Na/H antiporter in this setting (12).…”
Section: Resultsmentioning
confidence: 99%
“…On the basolateral side, bicarbonate can be transported via a Na/(HCO3)3 cotransporter or via chloride-coupled transporters. The overwhelming majority of bicarbonate reabsorption and cell pH regulation in the proximal tubule is dependent on sodium (2-8) while chloride removal does not affect the rates of bicarbonate reabsorption and the regulation of cell pH by acute changes in ambient Pco2 (4,7,8). Thus, the luminal Na/H antiporter and the basolateral Na/(HCO3)3 cotransporter are probably the two most important transporters involved in both transcellular bicarbonate transport and the cell pH response to changes in ambient Pco2.…”
Section: Introductionmentioning
confidence: 99%
“…Na/H antiporter activity was assayed as the Na-dependent increase in pH, after an acid load. This assay was performed in the absence of C02/HCO3 to eliminate any contribution from the Na(HCO3)2/Cl exchanger or the Na/3HCO3 cotransporter (26,27). The observation that amiloride inhibited most of the Na-dependent pHi recovery in proximal tubule cells and in fibroblasts confirms that this goal was achieved.…”
Section: Discussionmentioning
confidence: 98%
“…Comparison between cell pH response at acidic and alkaline pH is complicated by the fact that at acidic cell pH (induced by low luminal pH), the basolateral Na+:CO7 :HCO-cotransporter is reversed and works as an "alkaline loader." This is also the case when both luminal and peritubular pH and HCO-are increased (22).…”
Section: Resultsmentioning
confidence: 81%
“…Using the pH-sensitive dye BCECF, Krapf et al evaluated the role ofthe luminal Na+/H+ exchanger and basolateral Nae:CO7 :HCO-cotransporter in cell pH regulation in the intact perfused tubule (22). Increasing luminal pH increased and decreasing luminal pH decreased cell pH.…”
Section: Resultsmentioning
confidence: 99%